The Application of Flash Card Media Education to Improve Knowledge of Choosing Healthy Snacks among Elementary School Children at MIN 1 Kota Gorontalo - Syahrir, Akifa; Ngiu, Yessilia Pratiwi; Aswad, Ahmad (Fakultas Kedokteran, 2025)
Introduction: Snacking is a behavior closely associated with children. Children tend to consume snacks without paying attention to cleanliness or nutritional content. The knowledge among elementary school children regarding healthy snack choices remains relatively low, thus requiring educational interventions to improve their awareness. One effective method is flashcard-based education, which can serve as a visual and interactive learning medium to enhance children's understanding of healthy snack selection. Objective: This study aims to determine the effectiveness of flashcard-based education in improving knowledge about healthy snack choices among elementary school children. Method: This case study employed a descriptive research approach involving five children with low knowledge about healthy snacks. The intervention was conducted over one day using flash cards, and knowledge levels were assessed before and after the session. Results: Following the intervention, the children's knowledge scores increased significantly, from an initial score of 3 (low knowledge category) to a score of 8–10 (high knowledge category), reflecting an improvement of 5–6 points. Conclusion: Flash card-based education proves to be a beneficial learning tool in enhancing elementary school children's knowledge of healthy snack selection.